A fungal family of lytic polysaccharide monooxygenase-like copper proteins - Labourel, Aurore; Frandsen, Kristian E. H.; Zhang, Feng; Brouilly, Nicolas; Grisel, Sacha; Haon, Mireille; Ciano, Luisa; Ropartz, David; Fanuel, Mathieu; Martin, Francis; Navarro, David; Rosso, Marie-Noëlle; et al. (Nature chemical biology, 2020)
Lytic polysaccharide monooxygenases (LPMOs) are copper-containing enzymes that play a key role in the oxidative degradation of various biopolymers such as cellulose and chitin. While hunting for new LPMOs, we identified a new family of proteins, defined here as X325, in various fungal lineages. The three-dimensional structure of X325 revealed an overall LPMO fold and a His brace with an additional Asp ligand to Cu(II). Although LPMO-type activity of X325 members was initially expected, we demonstrated that X325 members do not perform oxidative cleavage of polysaccharides, establishing that X325s are not LPMOs. Investigations of the biological role of X325 in the ectomycorrhizal fungus Laccaria bicolor revealed exposure of the X325 protein at the interface between fungal hyphae and tree rootlet cells. Our results provide insights into a family of copper-containing proteins, which is widespread in the fungal kingdom and is evolutionarily related to LPMOs, but has diverged to biological functions other than polysaccharide degradation. The X325 protein family is highly similar to lytic polysaccharide monooxygenases (LPMOs) in regulation, structure and copper coordination by a histidine brace, yet lacks LPMO activity and suggests the evolution of an alternative function in fungi.